2017
DOI: 10.4209/aaqr.2016.07.0290
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Observation of the Mass and Chemical Composition of PM2.5 using an Automatic Analyzer in Kumamoto, Japan

Abstract: Due to economic growth in China, emissions of gaseous components from factories and automobiles have been increasing, which has resulted in severe air pollution. During the winter and spring seasons, Japan, which is on the leeward side of the Asian continent, is on the receiving end of this increasingly problematic transboundary air pollution. In this study, the mass concentration and chemical components of the particulate PM 2.5 were continuously observed using an automatic analyzer at Kumamoto on the west co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The chemical composition of PM receives attention because specific chemicals may play an important role in PM toxicity. Recent continuous measurements of aerosol chemical composition have shown that the Kyushu area in the west side of Japan is influenced by long-range transport from the Asian continent. They found that SO 2 and VOC are oxidized and converted to sulfate and low volatile oxygenated organic aerosols, respectively, during transport from the Asian continent. The ongoing efforts including PM sampling and its chemical analysis will be used for further epidemiological studies to characterize the health effects of PM composition.…”
Section: Epidemiological Studies and Related Field Studiesmentioning
confidence: 99%
“…The chemical composition of PM receives attention because specific chemicals may play an important role in PM toxicity. Recent continuous measurements of aerosol chemical composition have shown that the Kyushu area in the west side of Japan is influenced by long-range transport from the Asian continent. They found that SO 2 and VOC are oxidized and converted to sulfate and low volatile oxygenated organic aerosols, respectively, during transport from the Asian continent. The ongoing efforts including PM sampling and its chemical analysis will be used for further epidemiological studies to characterize the health effects of PM composition.…”
Section: Epidemiological Studies and Related Field Studiesmentioning
confidence: 99%
“…Therefore, it is essential to understand these processes to develop effective policy measures against air pollution. In the study of Misawa et al (2017), the mass concentration and chemical components of the particulate PM 2.5 were continuously observed using an automatic analyzer at Kumamoto on the west coast of Japan from October 2014 to March 2015. A greater number of high PM 2.5 days were observed in winter than in autumn.…”
mentioning
confidence: 99%